In Quest of Specific Teaching Methods for Reducing Spelling Mistakes and Enhancing Writing Outcome - ZELLOUMA, AHMED (Journal of Human Sciences, 2018)
The research paper in hand aims at investigating the effectiveness of teaching spelling rules as a means to reduce students’ orthographic mistakes, and consequently to improve their writing outcome. The population under study was Second Year Students of English at Constantine 1 University. Data collection in this research has been done using a teachers’ questionnaire and a students’ test. The teachers’ questionnaire, on the one hand, has revealed much information about different spelling-related aspects both on the part on the teachers and the students. Students’ test, on the other hand, has come check two major points in our study. The pre-test results seek out to reinforce the teachers’ questionnaire results. Meanwhile, the post-test results have confirmed the hypothesis we set at the beginning of the study: teaching spelling rules does indeed reduce students’ spelling mistakes and improve their writing outcome.